Strategic Policy Response to Climate Change in the Philippines Vol. 1: Portfolio of Climate Change Policies in Agriculture - Rebugio, Lucrecio; Ilao, Susan Sandra; Burgos, Bessie; Rogel, Carmen Nyhria; Sander, Björn Ole; Wassmann, Reiner (SEARCA and IRRI, 2018)
This publication features relevant information on climate change mitigation policies, particularly those pertinent to the Philippine agriculture sector. This would also be an important entry point for further policy research or deeper investigation of the translation of national climate change policies into ordinances and enabling mechanisms at the local level.